2016
DOI: 10.1021/acsami.6b07751
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot UV-Triggered o-Nitrobenzyl Dopamine Polymerization and Coating for Surface Antibacterial Application

Abstract: Dopamine (DA) protected by an o-nitrobenzyl functionality on its phenolic group was synthesized as a photolabile catecholamine derivative. This compound, o-nitrobenzyl dopamine (NBDA), was more stable than DA in basic solution at pH 8.5 and will not self-polymerize when protected from light. UV irradiation of a methanolic solution of NBDA at 365 nm for 40 min induced ca. 85% deprotection. Taking advantage of the stability of NBDA, a one-pot spray coating technique for modifying surfaces with polydopamine (PDA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Photolabile O‐protected DA as starting material in UV‐triggered PDA formation (top), oxidation of 3‐methyl‐4‐methoxyphenylethylamine with ammonium peroxydisulfate APS (bottom) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Photolabile O‐protected DA as starting material in UV‐triggered PDA formation (top), oxidation of 3‐methyl‐4‐methoxyphenylethylamine with ammonium peroxydisulfate APS (bottom) …”
Section: Resultsmentioning
confidence: 99%
“…Blocking one of the catechol hydroxyl groups of DA will block the dopamine quinone formation and thus the oxidative polymerization similar to PDA formation. for example, O ‐Nitrobenzylated dopamine (isomer mixture) was resistant to autoxidation by exclusion of light, but was applied for UV‐triggered (O‐deprotection) PDA coating by spray technique (Scheme ) …”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the membrane 8b had a better antibacterial activity than the membrane 8a , which might derive from the loading amount of H 2 O 2 on the surface (Table ). Moreover, this method allowed comparison and supplemented other antiseptic treatments, since Penicillin has been widely used in clinics for many years and has much less toxicity than most of other antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…Yet another challenge remaining is the fact that the use of chemical, thermal or photo-chemical reactions that allow coating process needs to be implemented directly on the implanted devices surrounded by host tissue. There are also some 'mild' coating methods [86][87][88][89][90][91][92][93] such as using catechol self-polymerization and surface functionalization chemistry, and photo-initiated crosslinking or surface-polymerization which should be further investigated to demonstrate biofilm treatment, recurrence prevention and tissue reintegration efficacy in vivo. Figure 8.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%